2012
DOI: 10.3109/02652048.2011.622054
|View full text |Cite
|
Sign up to set email alerts
|

The effect of treatment with a sustained-release prostacyclin analogue (ONO-1301-loaded PLGA microsphere) on short-term memory impairment in rats with transient global cerebral ischemia

Abstract: The purpose of this study was to prepare the ONO-1301 loaded poly(lactide-co-glycolide) microsphere (ONO-1301 PLGA MS) and to evaluate neuroprotective effects for short-term memory by a single subcutaneous injection of ONO-1301 PLGA MS on repeated induction of cerebral ischemia (2 × 10-min with a 1-min interval) in rat. Drug release profiles from ONO-1301 PLGA MS in vitro and in vivo were evaluated. The extent of ischemic injury was assessed behaviourally using the passive avoidance test and histopathologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Hazekawa et al [93] reported in 2012 that a single subcutaneous injection of ONO-1301SR into the rats that were subjected to repeated induction of cerebral ischaemia yielded a short-term functional and histopathological recovery. The same groups reported in 2012 that repeated ONO-1301SR administration reduced ischaemic damage of rats that were subjected to middle cerebral artery occlusion [94].…”
Section: Ono-1301/ono-1301sr Treatment For Extracardiac Pathologiesmentioning
confidence: 99%
“…Hazekawa et al [93] reported in 2012 that a single subcutaneous injection of ONO-1301SR into the rats that were subjected to repeated induction of cerebral ischaemia yielded a short-term functional and histopathological recovery. The same groups reported in 2012 that repeated ONO-1301SR administration reduced ischaemic damage of rats that were subjected to middle cerebral artery occlusion [94].…”
Section: Ono-1301/ono-1301sr Treatment For Extracardiac Pathologiesmentioning
confidence: 99%